Does size matter? The impact of changes in household structure on income distribution in Germany - Andreas Peichl; Nico Pestel; Hilmar Schneider (Center for Economic Studies and ifo Institute (CESifo), 2010)
Income inequality in Germany has been continuously increasing during the past 20 years. In general, this is understood as an increase in inequality of wages due to changes in bargaining power of employees. However, the role of changing household structure is widely neglected. Societal trends like a decline in birth rate and an increase in the risk of divorce affect per capita incomes, which has repercussions for the income distribution even if wages remain constant. The aim of this paper is to quantify the proportion of changing household structures in the increase in inequality. We find that the rise in inequality was indeed more due to changes of household structure and employment behavior rather than changes in wages. Moreover, a large part of this increase is compensated by the welfare state.
Keywords: D31; D63; J11; 330; income distribution; demography; household size; decomposition; Germany; Einkommensverteilung; Haushaltseinkommen; Privater Haushalt; Familiensoziologie; Deutschland